2007
DOI: 10.3892/or.18.6.1413
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neural cell adhesion molecule in salivary adenoid cystic carcinoma and its correlation with perineural invasion

Abstract: The expression of neural cell adhesion molecule (NCAM) was analyzed in immunohistochemical preparations from adenoid cystic carcinoma. The goal was to evaluate whether NCAM expression could be used as a biological marker for the perineural invasion of adenoid cystic carcinoma in the head and neck. The presence of perineural invasion and NCAM expression was evaluated in samples from 49 patients. Perineural invasion was identified in 33 of them (67%). A high incidence of perineural invasion was found in adenoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…These studies are based on correlations between NCAM1 expression in cancer cells, as seen in histologic specimens, and perineural invasion (29)(30)(31)(32)(33). Elevated NCAM1 expression has also been reported in nerves at sites of perineural invasion (48).…”
Section: Ncam1 Expression In Schwann Cells Promotes Perineural Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are based on correlations between NCAM1 expression in cancer cells, as seen in histologic specimens, and perineural invasion (29)(30)(31)(32)(33). Elevated NCAM1 expression has also been reported in nerves at sites of perineural invasion (48).…”
Section: Ncam1 Expression In Schwann Cells Promotes Perineural Invasionmentioning
confidence: 99%
“…NCAM1 expression has been correlated with the presence of perineural invasion in specimens from a variety of cancers (28)(29)(30)(31)(32)(33)(34) and has been reported to play a role in cancer progression and axon guidance (35)(36)(37)(38)(39)(40)(41). Three different shRNAs targeting NCAM1 (referred to herein as sh 1, sh 2, and sh 3, respectively) were used to generate stable cell lines in HEI-286 Schwann cells, and Western blot and immunofluorescence analysis revealed that sh 1 and sh 2 caused strong depletion, while sh 3 led to intermediate depletion of the 140-kDa NCAM1 isoform ( Figure 9A and Supplemental Figure 7A).…”
Section: Depletion Of Ncam1 In Schwann Cells Decreases Cancer Cell Inmentioning
confidence: 99%
“…However, the long-term outcome of these treatments is unfavorable (6). Several studies have identified clinicopathological factors in ACC with an unfavorable effect on survival, including old age, tumor location, advanced stage, solid histological subtype, high grade, tumor-node-metastasis (TNM) staging, major nerve involvement, the presence of perineural invasion, a positive surgical margin and lymph node metastasis (7,8). However, the real prognostic and recurrence factors are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although NCAM1 expression has previously been correlated with perineural invasion in clinical samples (20,21) and implicated in cancer progression and axonal guidance (22)(23)(24)(25), a role for NCAM1 in the regulation of perineural invasion has been unexplored. NCAM1 silencing in Schwann cells inhibited their ability to promote cancer cell invasion, protrusions, and recruitment to neurites.…”
Section: Ncam1 As a Molecular Mediator Of Perineurial Invasionmentioning
confidence: 99%